The Myth Of "The Red" in View of Islamic Boarding Schools - Kuny Salma Afifa; Alfian Setya Nugraha (Jurnal Disastri (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2024)
This study aims to describe myths in the view of Islamic boarding schools. This research uses Levi-Strauss theory and literature review approach and uses qualitative descriptive research methods. The source of this research was interviews with student audiences, female students and caregivers in Islamic boarding schools. Data collection techniques used are interviews, notes and supported by literature reviews in the form of articles. In this study tells about the myth of "The Red" circulating in girls' boarding schools. This myth is one of the things that is feared because the story circulating is very scary for female students. Myths in general have their own views in Islamic boarding schools. In this case, the researcher took the myth of "The Red" to be seen from the point of view of Islamic boarding schools.